Electron-driven and thermal chemistry during water-assisted purification of platinum nanomaterials generated by electron beam induced deposition - Warneke, Ziyan; Rohdenburg, Markus; Warneke, Jonas; Kopyra, Janina; Swiderek, Petra (Beilstein Journal of Nanotechnology, 2018)
Focused electron beam induced deposition (FEBID) is a versatile tool for the direct-write fabrication of nanostructures on surfaces. However, FEBID nanostructures are usually highly contaminated by carbon originating from the precursor used in the process. Recently, it was shown that platinum nanostructures produced by FEBID can be efficiently purified by electron irradiation in the presence of water. If such processes can be transferred to FEBID deposits produced from other carbon-containing precursors, a new general approach to the generation of pure metallic nanostructures could be implemented. Therefore this study aims to understand the chemical reactions that are fundamental to the water-assisted purification of platinum FEBID deposits generated from trimethyl(methylcyclopentadienyl)platinum(IV) (MeCpPtMe3). The experiments performed under ultrahigh vacuum conditions apply a combination of different desorption experiments coupled with mass spectrometry to analyse reaction products. Electron-stimulated desorption monitors species that leave the surface during electron exposure while post-irradiation thermal desorption spectrometry reveals products that evolve during subsequent thermal treatment. In addition, desorption of volatile products was also observed when a deposit produced by electron exposure was subsequently brought into contact with water. The results distinguish between contributions of thermal chemistry, direct chemistry between water and the deposit, and electron-induced reactions that all contribute to the purification process. We discuss reaction kinetics for the main volatile products CO and CH4 to obtain mechanistic information. The results provide novel insights into the chemistry that occurs during purification of FEBID nanostructures with implications also for the stability of the carbonaceous matrix of nanogranular FEBID materials under humid conditions.
Keywords: carbon contamination; electron induced reactions; focused electron beam induced deposition; nanostructure purification; platinum precursor

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - Noh, J. H.; Stanford, M. G.; Lewis, B. B.; Fowlkes, J. D.; Plank, H.; Rack, P. D. (Appl. Phys. A, 2014)

(untitled) - Utke, I.; Gölzhäuser, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Höflich, K.; Yang, R. B.; Berger, A.; Leuchs, G.; Christiansen, S. (Adv. Mater., 2011)

(untitled) - Winkler, R.; Schmidt, F.-P.; Haselmann, U.; Fowlkes, J. D.; Lewis, B. B.; Kothleitner, G.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Pablo-Navarro, J.; Sanz-Hernández, D.; Magén, C.; Fernández-Pacheco, A.; de Teresa, J. M. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Pohlit, M.; Eibisch, P.; Akbari, M.; Porrati, F.; Huth, M.; Müller, J. (Rev. Sci. Instrum., 2016)

(untitled) - Botman, A.; Mulders, J. J. L.; Hagen, C. W. (Nanotechnology, 2009)

(untitled) - Wnuk, J. D.; Gorham, J. M.; Rosenberg, S.; van Dorp, W. F.; Madey, T. E.; Hagen, C. W.; Fairbrother, D. H. (J. Phys. Chem. C, 2009)

(untitled) - Thorman, R. M.; Kumar T. P., R.; Fairbrother, D. H.; Ingólfsson, O. (Beilstein J. Nanotechnol., 2015)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Kolb, F.; Schmoltner, K.; Huth, M.; Hohenau, A.; Krenn, J.; Klug, A.; List, E. J. W.; Plank, H. (Nanotechnology, 2013)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Nanotechnology, 2013)

(untitled) - Villamor, E.; Casanova, F.; Trompenaars, P. H. F.; Mulders, J. J. L. (Nanotechnology, 2015)

(untitled) - Plank, H.; Noh, J. H.; Fowlkes, J. D.; Lester, K.; Lewis, B. B.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Gardener, J. A.; Golovchenko, J. A. (Nanotechnology, 2012)

(untitled) - Setthapun, W.; Williams, W. D.; Kim, S. M.; Feng, H.; Elam, J. W.; Rabuffetti, F. A.; Poeppelmeier, K. R.; Stair, P. C.; Stach, E. A.; Ribeiro, F. H.; Miller, J. T.; Marshall, C. L. (J. Phys. Chem. C, 2010)

(untitled) - Xue, Z.; Thridandam, H.; Kaesz, H. D.; Hicks, R. F. (Chem. Mater., 1992)

(untitled) - Engmann, S.; Stano, M.; Matejčík, Š.; Ingólfsson, O. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Warneke, J.; Van Dorp, W. F.; Rudolf, P.; Stano, M.; Papp, P.; Matejčík, Š.; Borrmann, T.; Swiderek, P. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Mackus, A. J. M.; Leick, N.; Baker, L.; Kessels, W. M. M. (Chem. Mater., 2012)

(untitled) - Koszinowski, K.; Schröder, D.; Schwarz, H. (Organometallics, 2003)

(untitled) - Landheer, K.; Rosenberg, S. G.; Bernau, L.; Swiderek, P.; Utke, I.; Hagen, C. W.; Fairbrother, D. H. (J. Phys. Chem. C, 2011)

(untitled) - Rosenberg, S. G.; Landheer, K.; Hagen, C. W.; Fairbrother, D. H. (J. Vac. Sci. Technol., B, 2012)

(untitled) - Hedhili, M. N.; Bredehöft, J. H.; Swiderek, P. (J. Phys. Chem. C, 2009)

(untitled) - Garrett, B. C.; Dixon, D. A.; Camaioni, D. M.; Chipman, D. M.; Johnson, M. A.; Jonah, C. D.; Kimmel, G. A.; Miller, J. H.; Rescigno, T. N.; Rossky, P. J.; Xantheas, S. S.; Colson, S. D.; et al. (Chem. Rev., 2005)

(untitled) - Maitlis, P. M. (Chem. Soc. Rev., 1981)

(untitled) - Shaver, A. (Can. J. Chem., 1978)

(untitled) - Labinger, J. A.; Herring, A. M.; Lyon, D. K.; Luinstra, G. A.; Bercaw, J. E.; Horvath, I. T.; Eller, K. (Organometallics, 1993)

(untitled) - Warneke, J.; Wang, Z.; Swiderek, P.; Bredehöft, J. H. (Angew. Chem., Int. Ed., 2015)

NIST Chemistry WebBook, NIST Standard Reference Database Number 69 - NIST Mass Spec Data Center (Mass Spectra, 2017)

(untitled) - Xue, Z.; Strouse, M. J.; Shuh, D. K.; Knobler, C. B.; Kaesz, H. D.; Hicks, R. F.; Williams, R. S. (J. Am. Chem. Soc., 1989)

(untitled) - Lersch, M.; Tilset, M. (Chem. Rev., 2005)

(untitled) - Lepage, M.; Michaud, M.; Sanche, L. (J. Chem. Phys., 1997)

(untitled) - Böhler, E.; Bredehöft, J. H.; Swiderek, P. (J. Phys. Chem. C, 2014)

(untitled) - Schmittel, M.; Burghart, A. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Chiu, I-C.; Kohn, H. (J. Org. Chem., 1983)

(untitled) - Ipolyi, I.; Michaelis, W.; Swiderek, P. (Phys. Chem. Chem. Phys., 2007)